Choledochal Cysts in Female Adult: Diagnostic Pitfall and Conservative Therapy for Bile Leak - Fuadhi, Singgih Annas; Barmawi, Agus; Sofii, Imam; Setyawan, Nurcahya; Handaya, Adeodatus Yuda (Smart Medical Journal, 2023)
Introduction: Choledochal cysts that are accompanied by obstructive jaundice are a rare case. These cysts can cause intrahepatic or extrahepatic ductal dilatation. Their diagnosis is difficult, particulary in adults. Proper management can prevent further complications.Methods: A serial case report of a patient with a choledochal cyst.Results: 2 female patients aged 21 years and 22 years have a painful and fixed lump in the upper right abdomen. The first patient also complained jaundice. Laboratory results showed an increase in total bilirubin and direct bilirubin. The second patient didn’t complaint about jaundice or increased bilirubin, and she had a cholecystectomy when she was ten. The diagnosis was confirmed by a contrast abdominal CT scan, showing type 1A Todani choledochal cysts in both patients. Management of the first patient was cyst excision, cholecystectomy, and Roux n Y hepaticojejunostomy. In the second patient, adhesiolysis, cyst excision, and Roux n Y hepaticojejunostomy were performed. The second patient had no postoperative complications.Conclusion: Choledochal cysts are a rare congenital condition in adulthood. n both cases, two patients were manage surgically. Bile leakage complications can be manage conservatively. Diagnostic and management of choledochal cysts must be correct to prevent pitfall and complications.